Strategi Guru dalam Mengatasi Kesulitan Belajar Tari: Studi Kasus di SMP Negeri 1 Randublatung, Indonesia - Siwi Sabilla Sekar Kinasih; Utami Arsih (Dinasti Research, 2026)
This study aims to identify dance learning difficulties and analyze teacher strategies in addressing them at SMP Negeri 1 Randublatung. The study employed a qualitative approach with a case study method. Data were collected through passive participant observation, in-depth interviews with teachers and students, and documentation. The results indicate that dance learning difficulties include wiraga (stiffness in movement), wirama (difficulty adjusting rhythm), and wirasa (lack of expression). Teachers implemented a combination of strategies: expository for introduction, cooperative for group practice, and affective for building self-confidence. The novelty of this research lies in the disclosure of combinative learning strategies (expository, cooperative, and affective) contextually in overcoming difficulties in learning dance in the aspects of wiraga, wirama, and wirasa at the junior high school level.